Speaking Skills for English As A Foreign Language in Video-Based Discussion - Razaq, Yusuf; Sri Widistari, Besse; Asyurah Khas, Suci; Amiruddin, Amiruddin; Satriani, Satriani (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This study focuses on determining if video-based discussions improve students' English-speaking abilities in their initial years at MTs As'adiyah Putra 1 Sengkang. Two classes served as the research sample in this study's true experimental design (the pretest-posttest control group design). There were 90 first-year students at MTs As'adiyah Putra 1 Sengkang in the population. 30 students served as the research's sample population. VII. A and VII. B was chosen as the sample for the research using the cluster random sampling approach, which was applied by the author. Speaking tests and the video-based discussion approach were used to gather data on the students' speaking abilities. The test's results were collated and put through a t-test and percentage analysis. As a result of the findings, it was determined that the probability value (0.00) was less than the threshold of significance (0.05) The examination of the data revealed that using video-based discussions to learn English considerably improves students' speaking abilities. The pre-test mean score is 1.9344, and the post-test mean score is 3.4817, which demonstrates this.